Improving the accuracy of prognostication in chronic myelomonocytic leukemia. Issue 8 (2nd August 2020) - Kaivers, Jennifer; Schuler, Esther; Hildebrandt, Barbara; Betz, Beate; Rautenberg, Christina; Haas, Rainer; Kobbe, Guido; Gattermann, Norbert; Germing, Ulrich
ABSTRACT: Introduction: Chronic myelomonocytic leukemia (CMML) is a hematological malignancy that is extremely variable regarding its clinical course. It may present either as a chronic disorder with mild symptoms and low disease burden for several years, thereby justifying a watch-and-wait-strategy, or may soon progress to acute myeloid leukemia (AML) leaving allogeneic stem cell transplantation as the only curative treatment option. Areas covered: Attempts have been made to integrate clinical, cytogenetic, and molecular parameters into scoring systems aiming at providing reliable prognostic information. In this article, we discuss several prognostic parameters and validate prognostic scores in a cohort of 645 patients with CMML. Expert opinion: We show that the CPSS (CMML prognostic scoring system) is a useful prognostic tool. The integration of molecular data into the new CPSS-mol will further improve prognostic accuracy, primarily by identifying an increased proportion of higher-risk patients.